1997
DOI: 10.1017/s0022215100137247
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical considerations of high jugular bulb in lateral skull base surgery

Abstract: In order to study high jugular bulb management in lateral skull base surgery, an anatomical study was conducted on 30 temporal bones by examining the relationship between the internal auditory canal (IAC) and the jugular bulb. The following parameters were measured: 1) Height of the jugular bulb (H) … distance between the level of the jugular bulb dome and the line passing through the confluence of the sigmoid sinus with the jugular bulb (SS-JB), 2) Mastoid length (ML) … distance between the mastoid process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…In an earlier report (Turgut and Tos, 1992), pneumatization of the mastoid bone was claimed as a cause of high JB; however, there are also some other researchers (Orr and Todd, 1988;Aslan et al, 1997) who advocate the idea that there is no relation between the position of the JB and pneumatization. In this study, the JB was found to be higher on the right side; however, no statistically significant differences were found between the COM group and the control group regarding the height of the JB.…”
Section: Discussionmentioning
confidence: 98%
“…In an earlier report (Turgut and Tos, 1992), pneumatization of the mastoid bone was claimed as a cause of high JB; however, there are also some other researchers (Orr and Todd, 1988;Aslan et al, 1997) who advocate the idea that there is no relation between the position of the JB and pneumatization. In this study, the JB was found to be higher on the right side; however, no statistically significant differences were found between the COM group and the control group regarding the height of the JB.…”
Section: Discussionmentioning
confidence: 98%
“…This region is often the site of vascular, inflammatory, neoplastic, or traumatic lesions, and surgical or (Zimmerman and Seifert, 1997;Ozveren et al, 2002). In cranial base surgery, the anterior transpetrosal approach offers the possibility of removing invasive petroclival lesions extending into the posterior fossa, the cavernous sinus, and the extradural space around the petrous apex (Aslan et al, 1997;Ozveren et al, 2002;Turgut et al, 2003). It is an indisputable fact that the success in surgical strategy and planning mainly relies on the surgeon's knowledge of the superficial anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The asterion, defined as the junction of the lambdoid, parietomastoid, and occipitomastoid sutures, has been advocated as a primary landmark in performing combined petrosal approaches to the cranial base (Williams et al, 1995;Aslan et al, 1997;Day and Tschabitscher, 1998;Aziz et al, 2000). But there has also been some doubt requiring its reliability as a landmark (Yamashima et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This bony phase and the successive ones are safer in petrous bones with "large" mastoids [≥ 35 mm long, according to Aslan et al 3 ] because it is possible to obtain a wider surgical corridor and a better working burr hole angle. This consideration also holds for Trautmann's triangle.…”
Section: Resultsmentioning
confidence: 99%